Pengukuran Value At Risk (Var) Saham Perbankan Dalam Indeks IDX30 Dengan Metode Simulasi Historis - wahdini wahdini; Media Rosha (Journal of Mathematics UNP, 2021)
The problem of the investor is to determine assets for invested until gets profits and not losses. Calculate value the risk using the measurement Value at Risk. The method used Historical Simulation Method by ignoring the normality and time series. This research using secondary data,  closing price daily data  of the stock banking listed on the IDX30 index in the period August 2020 - July 2021. Calculate data analysis of the daily return of a stock, determine the confident level  and time period, estimate the maximum loss and calculate the value of the VaR of each stock. Based on the results of the research  when the range of confident  95%, the time series of one day and the initial investment is assumed to Rp.100.000.000 to six banking stocks that BBCA Rp. 2.189.429, BBNI Rp.3.176.740, BBRI Rp. 3.129.625, BBTN Rp. 3.939.326, BMRI Rp. 3.348.373 and BTPS  Rp.3. 953.960.